The Selling of the South: The Southern Crusade for Industrial Development, 1936-1990, 2nd edition - Dick, W. M. (Labour / Le Travail, 1994)
The article reviews the book, "The Selling of the South: The Southern Crusade for Industrial Development, 1936-1990," 2nd edition, by James C. Cobb.
Keywords: BOOKS – Reviews; COBB; James C.; INDUSTRIALIZATION; Nonfiction; SELLING of the South: The Southern Crusade for Industrial Development 1936-1990; The (Book)